Application of sulfonic acid functionalized nanoporous silica (SBA-Pr-SO3H) in the solvent free synthesis of (E)-arylidene-1,3-dihydroindole-2-ones - Gholamzadeh, Parisa; Ziarani, Ghodsi Mohammadi; Badiei, Alireza; Bahrami, Zohreh (European Journal of Chemistry, 2012)
An efficient and green condensation reaction is developed for the synthesis of (E)-arylidene-1,3-dihydroindole-2-ones; (1), using heterogeneous nanoporous acid catalyst of SBA-Pr-SO3H with pore size, 6 nm in solvent free condition. Arylidene-1,3-dihydroindole-2-ones have many pharmaceutical properties such as Tyrosin kinase inhibiton. This method has the advantages of short reaction time, isolation ease of the products, excellent yields and recyclable catalyst.